2000
DOI: 10.1139/f99-180
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing invertebrate communities in prairie wetlands: a multivariate approach

Abstract: We examined the relationships between invertebrate community structure and a number of biotic and abiotic variables in 19 semipermanent prairie wetlands. We tested whether aquatic invertebrate communities differed (i) between wetlands with and without fathead minnows (Pimephales promelas) and (ii) according to drainage history of wetlands (restored versus natural, nondrained). We also evaluated influences of other environmental variables on invertebrate community structure, including abundance of aquatic macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(71 citation statements)
references
References 28 publications
5
65
0
1
Order By: Relevance
“…Several studies suggested that the hydroperiod influences the structure of wetland macroinvertebrate communities (Wellborn et al, 1996;Zimmer et al, 2000). Our study showed that the mollusc richness and composition were similar both in permanent and intermittent wetlands.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Several studies suggested that the hydroperiod influences the structure of wetland macroinvertebrate communities (Wellborn et al, 1996;Zimmer et al, 2000). Our study showed that the mollusc richness and composition were similar both in permanent and intermittent wetlands.…”
Section: Discussionsupporting
confidence: 62%
“…The macroinvertebrate structure in wetlands has been associated with area and habitat heterogeneity (Oertli et al, 2002;Batzer et al, 2004;Panatta et al, 2006;Studinski and Grubbs, 2007;Stenert et al, 2008); hydroperiod (Tarr et al, 2005;Whiles and Goldowitz, 2005;Stenert and Maltchik, 2007); altitude (Oertli et al, 2002;Jacobsen, 2004); water chemistry (Heino, 2000;Batzer et al, 2004), and water depth and temperature (Zimmer et al, 2000;Hall et al, 2004;Tarr et al, 2005;Studinski and Grubbs, 2007). However, most of these surveys were developed in the North Hemisphere and Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have determined the main environmental factors controlling processes and patterns of macroinvertebrate community structure and function (e.g., ORMEROD, 1987;ZIMMER et al, 2000;AGUIAR et al, 2002;TRIGAL et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental conditions (oxygen content, water transparency, light and nutrients availability, species composition and distribution of submerged macrophytes) may influence the variance and distribution of epiphytic fauna (Demeke, Ahma 1999;Zimmer et al 2000;Elizabeth et al 2003;Roberts et al 2003;Peter et al 2004). Two shallow lakes of Polesie Lubelskie were selected for the study.…”
Section: Introductionmentioning
confidence: 99%